Medjugorje and the Supernatural: Science, Mysticism and Extraordinary Religious Experience by Daniel Maria Klimek - Roney-Dougal, Serena (Journal of Scientific Exploration, 2019)
The author of this well considered and finely argued book is a Franciscan friar and an assistant professor of theology. This book is a much later and revised draft of his postgraduate thesis. With nearly a hundred pages of notes, references and index, it has been written by an academic for others in his field. I am neither a philosopher nor a theologian, so my, of necessity brief, review is that of a lay person for other lay people. Klimek, according to the blurb, is an authority on the phenomena experienced at Medjugorje, Croatia, where several young people claimed to have had visions of the Blessed Virgin Mary (BVM) in the early 1980’s. More than thirty years later, some of them are still claiming to have daily visions, so this is a very long running phenomenon. BVM visions have occurred at several places in Europe, most notably Lourdes, all of them to people who follow the Roman Catholic religion. In a Marian vision, the experiencers claim that they are seeing the BVM and that she is conversing with them. Only the visionaries see her. Usually these are people in their late teens or early twenties. Others who attend do not have the same trance ecstasy experience and rely on the reporting of the visionaries. Klimek relates some of the conversations the Medjugorje visionaries have had with the BVM, which are all consistent with Catholic doctrine. As far as I understand it, Klimek is arguing that these visions are not the result of cultural associations, hallucinations, imaginations, etc., but are divinely inspired and part of what he calls the perennial tradition. This tradition considers that visionary experiences are worldwide and have a universal basis independent of the culture in which they appear. The other stream of opinion he calls the constructivist, where people argue that we construct our visionary experiences out of our cultural associations, imagination, etc. As far as I know Marian visions have only been experienced in countries where there are Roman Catholics, so he is having to argue pretty hard to align these visionaries with the perennial rather than the constructivist opinions. He uses the words epistemology and hermeneutics repeatedly, often several times within the same page. I am not familiar with these words, and though I think I understand them, and I most certainly recognise that they are necessary for his fellow theological academics, for myself as a lay person they didn’t help me understand his argument, and made for very slow and careful reading.